Custeio direto: elemento de apoio na tomada de decisão - Machado, Renato Brandão (1983)
The dissertation aims to present a costing method called.direct costing and its utilization for entreprises' decision making. The dissertation covers five topics: In the first one, it includes a revision of some necessary points for the understanding of the problems of this dissertation. The second topic classifies and analyses the costs in relation to their behaviours, we show their associability and variability. The third topic shows the ielationship between prices, cost, volume and profit, as well as, the contribution analysis. The fourth topic presents the conventional method of costing or absorption costing and he distinction between this and management method or direct costing. Finally, the fifth topic analyses the direct costing procedure and its effect on entreprises' decisions, associated with the bperations's earnings. We can ftnd some softwares annexed for the personal computer HP-41 CV, that aiaim at the solution of some problems found during the work.